2023
DOI: 10.5430/wjel.v14n2p101
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Maintenance Amongst Sojourner Saudi Families After Returning to Their Home Country

Awatif Alshammri

Abstract: This study explores the language planning efforts for English language maintenance employed by sojourning Saudi families after returning to their home country. The study concludes that the importance of English in the development of different sectors in Saudi Arabia and the advantages of bilingualism in economic, health, and cognitive aspects for children played a significant role in the families’ language planning decisions. The study showed that the mothers maintained and developed their children’s English t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Students also have a passion for learning English words to understand the conversations they hear through YouTube, and English programs, especially through mobile phones (Vimochana, et al, 2023), (Raj & Baisel, 2024). Parents' encouragement of students to learn English helped enhance the role of primary school in students' acquisition of English language skills (Alshammari, 2024). It can also be explained that listening skills for short sentences were ranked first in the listening skills axis by saying that students prefer to listen to sentences that convey an integrated meaning, more than listening to single words, and this is consistent with a study (Carmen et al, 2024).…”
Section: Published By Sciedu Presssupporting
confidence: 80%
See 3 more Smart Citations
“…Students also have a passion for learning English words to understand the conversations they hear through YouTube, and English programs, especially through mobile phones (Vimochana, et al, 2023), (Raj & Baisel, 2024). Parents' encouragement of students to learn English helped enhance the role of primary school in students' acquisition of English language skills (Alshammari, 2024). It can also be explained that listening skills for short sentences were ranked first in the listening skills axis by saying that students prefer to listen to sentences that convey an integrated meaning, more than listening to single words, and this is consistent with a study (Carmen et al, 2024).…”
Section: Published By Sciedu Presssupporting
confidence: 80%
“…The results of the fourth question can be interpreted that media education contributed to enhancing both listening and speaking skills in English for primary school students, as teachers reported that media education and school Radio contributed to the students' passion for listening to English words, short and long sentences, and repeating the words they heard. This may be due to the primary school's keenness to teach students English language skills, especially through school Radio, and this is consistent with a study (Alshammari, 2024). The teachers encourage the students to learn the English language.…”
Section: Published By Sciedu Presssupporting
confidence: 69%
See 2 more Smart Citations